The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1253/circj.cj-21-0169
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Features of Venous Thromboembolism in Hospitalized Patients With Coronavirus Disease 2019 (COVID-19) in Japan

Abstract: respiratory syndrome coronavirus 2, but it can also cause thromboembolic complications through coagulopathy. 3,4 In particular, several studies reported a high prevalence of venous thromboembolism (VTE), including pulmonary embolism (PE) and deep vein thrombosis (DVT) in hospi-T he coronavirus disease 2019 (COVID-19) was first reported in Wuhan, China, in December 2019, and has become a huge threat worldwide as a pandemic. 1,2 The main pathophysiology of COVID-19 is a respiratory infectious disease caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Our study revealed that thrombotic complications developed more frequently in patients with a severe respiratory disease on admission and were associated with death, consistent with the previous findings in the Japanese population (16). Additionally, elevated D-dimer and ferritin levels on admission were the risk factors for the development of thrombosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study revealed that thrombotic complications developed more frequently in patients with a severe respiratory disease on admission and were associated with death, consistent with the previous findings in the Japanese population (16). Additionally, elevated D-dimer and ferritin levels on admission were the risk factors for the development of thrombosis.…”
Section: Discussionsupporting
confidence: 91%
“…So far, there is limited evidence about the incidence of thrombosis and the association of biomarkers in Japanese population, except a few (15)(16)(17)(18). The objective of the current study was to identify the risk factors for the development of thrombosis.…”
Section: Introductionmentioning
confidence: 97%
“…Yamashita et al, conducting questionnaire surveillance involving 1243 patients with COVID-19 among 77 institutions in Japan, reported a low prevalence of venous thrombosis (0.6%, 7/1243) and PE (0.4%, 5/1243) [10]. In line with our data that the proportion of thromboembolic events was up to 44.4% (4/9) in patients with severe COVID-19 infection requiring mechanical ventilation, one Japanese multicenter cohort study with 1236 patients with COVID-19 infection found that the prevalence of CTproven venous thromboembolism was up to 40% in those with severe COVID-19 infection requiring mechanical ventilation [22]. Therefore, more studies for thromboembolic events are warranted to address the epidemiology of thromboembolic events among patients with COVID-19 in Asian populations, particularly studies with active surveillance.…”
Section: Discussionsupporting
confidence: 88%
“…However, recent studies have shown that the incidence of VTE in Asian countries, including Taiwan, has risen in the past two decades, and the increased incidence may be attributed to increased vigilance for VTE, ageing population, increased patients with cancer, and altered lifestyle [17][18][19][20]. Notably, accumulating evidence have shown the highly prevalent thromboembolic events in patients including the Asian population with COVID-19 infection, particularly those with high disease severity and elevated levels of D-dimer [4,8,21,22]. Ren et al carried out a cross-sectional study with a routine survey for DVT using compression ultrasound examinations among 48 patients with severe COVID-19 infection requiring ICU admission in Wuhan [4].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high risk of VTE in COVID-19 patients, it could be important for clinicians to conduct an appropriate imaging examination of these patients when they are suspected of VTE during the course of COVID-19 treatment to avoid under-diagnosis of VTE. However, a previous study reported that only a small number of patients were evaluated with contrastenhanced computed tomography (CT) examination in real-world clinical practice, which suggests some reluctance to conduct imaging examinations due to the risk of infection to healthcare providers (2). Thus, practical diagnostic strategies for VTE could be clinically relevant.…”
Section: Covid-19 and Venous Thromboembolismmentioning
confidence: 99%